2014
DOI: 10.1186/1472-6750-14-74
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of human acidic fibroblast growth factor 1 in the medicinal plant, Salvia miltiorrhiza, accelerates the healing of burn wounds

Abstract: BackgroundHealing of burns is a complex process and very few effective treatments exist to facilitate the burn recovery process. Human acidic fibroblast growth factor 1 (FGF-1) plays an important role in a variety of biological processes, including angiogenesis, and tissue repair. Salvia miltiorrhiza is widely used in traditional Chinese medicine as an herb for the treatment of various diseases, including cardiovascular and cerebrovascular diseases, and traumatic injuries. We present that expression of FGF-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Huangqi contains glycosides and flavonoids as the main components, which have been shown to improve VEGF mRNA expression in vascular endothelial cells 8,14) . However, several researchers have reported that the activity of cyclooxygenase-2 (COX-2) may be inhibited by high concentrations of flavonoid [8][9][10]12,14) , which may explain for the diminished angiogenic activity in the specimens containing 10 wt% Huangqi in the present study. Similarly, diminished angiogenic activity in the specimens containing Danshen may be attributed to the high amounts of Salvianolic Acid B in this drug, which is known to inhibit the activities of TGF-β and COX-2 8,10,14,15) .…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Huangqi contains glycosides and flavonoids as the main components, which have been shown to improve VEGF mRNA expression in vascular endothelial cells 8,14) . However, several researchers have reported that the activity of cyclooxygenase-2 (COX-2) may be inhibited by high concentrations of flavonoid [8][9][10]12,14) , which may explain for the diminished angiogenic activity in the specimens containing 10 wt% Huangqi in the present study. Similarly, diminished angiogenic activity in the specimens containing Danshen may be attributed to the high amounts of Salvianolic Acid B in this drug, which is known to inhibit the activities of TGF-β and COX-2 8,10,14,15) .…”
Section: Discussionmentioning
confidence: 48%
“…We performed an angiogenesis test in the group using PEMA-A polymer (powder form) due to the high tan δ values exhibited by this group. Several in vitro and in vivo method have been used to evaluate angiogenesis [8][9][10][11]26) . The various in vivo methods used include the Mile's assay, chicken embryo chorioallantoic membrane method, and the Matrigel subcutaneous implantation method; however, these methods have various limitations 26) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of plant based strategies is opening a new perspective for the treatment of skin wounds, mainly in developing countries, once it represents a simple, low cost, and affordable therapy [1, 7, 5658]. There are several studies indicating beneficial effects of herbal medicines in all phases of the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that flaws on the leukocyte recruitment and function can impair the healing process due to reductions in the synthesis of regulatory molecules that drives the extracellular matrix assembly [57] and neoangiogenesis [8]. In this way, the development of drugs and alternative treatments that favor the migration and cellular activity during the inflammatory and proliferation phases may enhance the skin wound repair.…”
Section: Introductionmentioning
confidence: 99%